Design and realization of binder-free electrodes with leaf-like structure based on Fe-Co binary oxides/graphene enabling efficient energy storage of flexible solid-state supercapacitors. (June 2022) - Su, Siyu; Dai, Huimin; Lin, Yueming; Xiang, Xiaoyan; Jiang, Yue; Zhu, Xiaohong
Abstract: High performance and efficient preparation of electrodes are prerequisites for energy storage devices to adapt to complex usage scenarios in the future. In this work, flexible binder-free electrodes with unique leaf-like structure were designed and prepared based on Fe-Co binary oxides nanoparticles/graphene coated on carbon cloth, which can be directly used in supercapacitors without any subsequent operations or additives. Morphological characterization demonstrates that the structure of the electrodes is similar to that of a leaf, including veins (carbon fibers), blades (graphene layers), and mesophyll cells (evenly distributed CoO particles of 60–80 nm and Fe3 O4 particles less than 10 nm). Electrochemical characterization confirms that the electrode exhibits high specific capacitance of 458 F g −1 at 1 A g −1 under a wide operating potential window of 1.45 V. After assembled into a flexible solid-state symmetric supercapacitor with aqueous KOH/PVA as the gel electrolyte, the device exhibits good energy density (20.2 Wh kg −1 ), ameliorated power density (8910 W kg −1 ), and excellent cycling stability (capacitance retention of 87% after 3000 continuous cycles at 1 A g −1 ). Furthermore, after being bent at 60°, 120°, 180° and finally restored to the original state, its cyclic voltammetry curve remains almost unchanged in both shape and area, indicative of its remarkable flexibility and structural stability. All the results prove that this work is promising to further promote the development of supercapacitors. Graphical abstract: Unlabelled Image Highlights: Binder-free electrodes with unique leaf-like structure are designed and realized by a dip-coating strategy. The electrode exhibits high specific capacitance of 458 F g -1 at 1 A g -1 under a wide potential window of 1.45 V. The solid-state supercapacitors exhibit better energy and power densities compared to previously reported devices. The supercapacitors are endowed with excellent flexibility without performance degradation in multiple folded states.